Prognostic value of quantitative flow ratio in patients with coronary heart disease after percutaneous coronary intervention therapy: a meta-analysis - Chen, Huaigang; Hong, Lang; Xi, Gang; Wang, Hong; Hu, Jing; Liu, Qi; Yang, Liu (Frontiers in Cardiovascular Medicine, 2023)
Background Coronary atherosclerotic heart disease is one of the most serious health and life-threatening diseases. There is no doubt that despite the increasing number of assessment methods used clinically, the prognosis assessment is still not ideal, and newer assessment methods are needed. Objective To investigate the predictive value of quantitative flow ratio (QFR) for adverse events (vessel-oriented composite endpoint events/target lesion failure) in patients after percutaneous coronary intervention (PCI). Method Eight studies involving 4,173 patients (5,688 vascular lesions) were included. These are studies on the relationship between QFR values and prognosis of adverse cardiac events after PCI. This meta-analysis was performed after quality assessment and data extraction of clinical trials data that met the inclusion criteria. Result Each of the eight studies described the cut-off values for the best predictive ability of post-PCI QFR and the hazard ratio (HR) between QFR values and adverse events, respectively. The pooled HR of these studies was 4.72 (95% CI: 3.29–6.75). Concurrently, lower post-PCI QFR values were associated with the occurrence of individual clinical events (cardiac death/myocardial infarction/target vessel revascularization), with relative risk values of 6.51 (95% CI: 4.96–8.53), 4.83 (95% CI: 3.08–7.57), and 4.21 (95% CI: 2.66–6.68), respectively. Conclusion QFR may have great potential in the assessment of prognosis. It is necessary to measure QFR value after PCI. A lower QFR value after PCI was an important predictor for experiencing adverse events.